1970
DOI: 10.3329/jom.v11i2.5453
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Acute Stroke and Metabolic Syndrome

Abstract: Objective: Metabolic syndrome is the cluster of vascular risk factors including insulin resistance, elevated bloodpressure, hyperlipidemia, and obesity. Metabolic syndrome is strongly associated with cardiovascular andcerebrovascular disease. The aim of this study is to find out association between stroke and metabolic syndrome inour population.Methods: In this observational study, a total number of fifty randomly selected patients were studied from July2009 to December 2009 at Medicine ward of Dhaka Medical C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Although 46% of patients observed had metabolic syndrome, overall, a higher contribution was seen in the IS cases (65·2%) than in the HS cases (34·8%). Of the 54% of patients without metabolic syndrome, 55·6% were HS patients (9). Atherogenic dyslipidaemia is characterized by increased triglyceride (TG) levels (TG ≥ 150 mg/dl) and decreased high-density lipoprotein (HDL) levels (HDL ≤40 mg/dl) (8).…”
Section: Prevalence and Incidencementioning
confidence: 99%
See 3 more Smart Citations
“…Although 46% of patients observed had metabolic syndrome, overall, a higher contribution was seen in the IS cases (65·2%) than in the HS cases (34·8%). Of the 54% of patients without metabolic syndrome, 55·6% were HS patients (9). Atherogenic dyslipidaemia is characterized by increased triglyceride (TG) levels (TG ≥ 150 mg/dl) and decreased high-density lipoprotein (HDL) levels (HDL ≤40 mg/dl) (8).…”
Section: Prevalence and Incidencementioning
confidence: 99%
“…Atherogenic dyslipidaemia is characterized by increased triglyceride (TG) levels (TG ≥ 150 mg/dl) and decreased high-density lipoprotein (HDL) levels (HDL ≤40 mg/dl) (8). The data indicated that the majority (64%) of stroke patients had high TG levels and 68% had low HDL levels (9). However, the actual TG and HDL levels were not reported.…”
Section: Prevalence and Incidencementioning
confidence: 99%
See 2 more Smart Citations